Preparation, crystallization and preliminary X-ray crystallographic studies of diadenosine tetraphosphate hydrolase from Shigella flexneri 2a - Hu, Wenxin (International Union of Crystallography, 2005)
Diadenosine tetraphosphate (Ap(4)A) hydrolase (EC 3.6.1.41) hydrolyzes Ap(4)A symmetrically in prokaryotes. It plays a potential role in organisms by regulating the concentration of Ap(4)A in vivo. To date, no three-dimensional structures of proteins with significant sequence homology to this protein have been determined. The 31.3 kDa Ap(4)A hydrolase from Shigella flexneri 2a has been cloned, expressed and purified using an Escherichia coli expression system. Crystals of Ap(4)A hydrolase have been obtained by the hanging-drop technique at 291 K using PEG 550 MME as precipitant. Ap(4)A hydrolase crystals diffract X-rays to 3.26 Å and belong to space group P2(1), with unit-cell parameters a = 118.9, b = 54.6, c = 128.5 Å, β = 95.7°.